XALQARO OLIMPIYA HARAKATINING RIVOJLANISH TARIXI - Mambetov, B.J. (SCIENCE and SOCIETY, 2022)
This article illustrates the history of the development of the International Olympic movement, which informs about each period of development of the International Olympic movement, the factors that motivate it, as well as the achievements.